2017
DOI: 10.1007/s00270-016-1556-2
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Gastric Conditioning by Preoperative Arterial Embolization Before Oncologic Esophagectomy: A Single-Center Experience

Abstract: Preoperative ischemic conditioning by arterial embolization before oncologic esophagectomy seems to be effective in preventing anastomotic leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Despite promising results in experimental studies, when translated to humans, IGP has failed to exhibit a clear advantage in terms of AL reduction following esophageal resection [ 10 , 11 , 12 , 13 , 14 ]. Yet, the clinical trials using IGP are highly heterogeneous in terms of technique (angiographic embolization [ 36 , 37 , 38 ] or laparoscopic vessels ligation [ 16 , 18 , 39 , 40 , 41 , 42 ]) and number of vessels involved, and they are mostly of retrospective nature. Importantly, the delay between preconditioning and esophagectomy is largely variable in those studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite promising results in experimental studies, when translated to humans, IGP has failed to exhibit a clear advantage in terms of AL reduction following esophageal resection [ 10 , 11 , 12 , 13 , 14 ]. Yet, the clinical trials using IGP are highly heterogeneous in terms of technique (angiographic embolization [ 36 , 37 , 38 ] or laparoscopic vessels ligation [ 16 , 18 , 39 , 40 , 41 , 42 ]) and number of vessels involved, and they are mostly of retrospective nature. Importantly, the delay between preconditioning and esophagectomy is largely variable in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…Authors using an endovascular approach reported better results in terms of increased GCF perfusion [ 36 ] or even AL reduction [ 38 ] as compared to the ones using laparoscopy. In fact, the largest patient series using laparoscopic IGP describe shorter time intervals than 2 weeks [ 40 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complications of the preoperative arterial embolization have been reported in the literature. The most frequent are mild abdominal pain, nausea and splenic infarction and necrosis (33)(34)(35)37,38). In one case, hospital stay longer than 48 hours was described (37).…”
Section: Percutaneous Conditioning By Interventional Radiologymentioning
confidence: 95%
“…Seven studies describe the experience with percutaneous ischemic conditioning with embolization (10,(33)(34)(35)(36)(37)(38). In all of them, the procedure protocol includes embolization of RGA, LGA and SA, in a variable period before surgery (5 to 21 days).…”
Section: Percutaneous Conditioning By Interventional Radiologymentioning
confidence: 99%